Emerging research trends in green finance: A bibliometric overview - Sagarika Mohanty; Sudhansu Sekhar Nanda; Tushar Soubhari; Vishnu N S; Sthitipragyan Biswal; Shalini Patnaik (Journal of Risk and Financial Management, 2023)
Green finance is significant since it is the first organized effort by the financial industry to link financial performance with a positive environmental impact. Green finance products are being developed appropriately to achieve sustainability. The present study employs a fundamental bibliometric methodology to assess the current state and progress of academic research on green finance. 1748 papers are taken for this study. Data are extracted from a scholarly database i.e., SCOPUS and for network analysis, VOSviewer software is used. The present paper is focused on six research questions. Information is gathered to examine the above research questions and network maps are applied. We examined year-wise document publications, types of documents, subject areas, most influential articles, different journal sources, co-authorship of countries, and co-occurrence of keywords of green finance. We categorized keywords into clusters and discovered new trends in green finance. The paper also highlighted the recent issues and challenges. The study has also certain limitations and it is concluded by providing implications and suggestions for future studies. At last, this paper will give more insights to researchers, academicians, and others to discover the research gaps in this field of green finance.
Keywords: 650; bibliometric analysis; financial markets; green finance; green initiatives; green investment; network analysis; sustainable finance; VOSviewers